(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The article analyzes the issue of protecting children’s lives during the Second World War with the help of archival sources and scientific literature. Also, the article revealed that “bread cards” were introduced in the republic in order to regulate the food shortage that occurred since 1941, and that only urban residents used it, and class and social separation was observed in its distribution.